2022
DOI: 10.2478/ijcss-2022-0010
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Blended Learning and Direct Video Feedback on Primary School Students’ Three-Step Ball Throwing Technique

Abstract: The purpose of this study was to evaluate three distinct methods of teaching the three-step ball throw simulating the javelin throw technique to primary school students. The sample consisted of 131 primary school students of 5th and 6th grade (Mage = 11.4, SD = 0.47 years) randomly divided into three groups. The control group (CON) received typical instruction, the first experimental group (EXP) followed a blended learning intervention which included an interactive learning activity software and the second exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 81 publications
(76 reference statements)
0
0
0
Order By: Relevance
“…Likewise, the research by Kyriakidis et al [58], reported that the implementation of BT in the PE class could help studentathletes to have good javelin throwing skills. Basically, the main advantage of BT is collaborating face toface teaching and technology [59,52,60], thus creating a positive innovation in learning [38].…”
Section: Discussionmentioning
confidence: 98%
“…Likewise, the research by Kyriakidis et al [58], reported that the implementation of BT in the PE class could help studentathletes to have good javelin throwing skills. Basically, the main advantage of BT is collaborating face toface teaching and technology [59,52,60], thus creating a positive innovation in learning [38].…”
Section: Discussionmentioning
confidence: 98%
“…Athletics coaches are highly recommended (Schmolinsky, 1983) to present a series of photographs or films, both for learning and for the evaluation of their athletes' technique. Recent research revealed that this approach is effective (Kyriakidis et al, 2022a;2022b). Nevertheless, the implementation of the results of biomechanical reports of elite athletes to novices or lower-level athletes without "filtering" this information through the model depicted in Figure 1 is not the most appropriate approach to effectively use the image-based information in the training/learning process.…”
Section: Methodological Aspects Of Sport Technique Trainingmentioning
confidence: 99%